Assessing the Concurrent Validity of the Revised Kinder, Lydenberg, and Domini Corporate Social Performance Indicators. (September 2015) - Hart, Timothy A.; Sharfman, Mark
This article examines the concurrent validity of the Kinder, Lydenberg, Domini Research & Analytics (KLD) corporate social performance (CSP) measures. Because KLD changed its evaluation methods to richer approaches, a new look at the concurrent validity of the indicators is necessary. To do this new look, the authors examine the new "Binary" and "Continuous" versions of the KLD and compare them with previous versions of KLD. The results suggest that the continuous scores provide better measurement characteristics than do the binary version. Overall, the new versions of the KLD data demonstrate concurrent validity with the original version.